The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41467-023-36448-6
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves swallowing function in a post-stroke dysphagia mouse model by activating the motor cortex inputs to the nucleus tractus solitarii through the parabrachial nuclei

Abstract: As a traditional medical therapy, stimulation at the Lianquan (CV23) acupoint, located at the depression superior to the hyoid bone, has been shown to be beneficial in dysphagia. However, little is known about the neurological mechanism by which this peripheral stimulation approach treats for dysphagia. Here, we first identified a cluster of excitatory neurons in layer 5 (L5) of the primary motor cortex (M1) that can regulate swallowing function in male mice by modulating mylohyoid activity. Moreover, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 90 publications
7
47
0
Order By: Relevance
“…Our previous study showed that swallowing function was impaired after NTS inhibition, and EA rescued the expression of c-Fos-positive neurons in PSD model mice, 25 which confirmed the role of the NTS in swallowing function. To further observe the role of the NTS in the regulation of swallowing function by M1, optogenetic activation and chemogenetic inhibition viruses (AAV2/9-CaMKIIα-ChR2, AAV2/9-CaMKIIα-hM4Di) were injected into the M1 and NTS, respectively (Figure 3A).…”
Section: The Role Of the Nts In Swallowing Responses Induced By The A...supporting
confidence: 57%
See 1 more Smart Citation
“…Our previous study showed that swallowing function was impaired after NTS inhibition, and EA rescued the expression of c-Fos-positive neurons in PSD model mice, 25 which confirmed the role of the NTS in swallowing function. To further observe the role of the NTS in the regulation of swallowing function by M1, optogenetic activation and chemogenetic inhibition viruses (AAV2/9-CaMKIIα-ChR2, AAV2/9-CaMKIIα-hM4Di) were injected into the M1 and NTS, respectively (Figure 3A).…”
Section: The Role Of the Nts In Swallowing Responses Induced By The A...supporting
confidence: 57%
“…Data are presented as the mean ± SD, and n indicates the number of biologically independent samples (mice) per group.regulated by EA at CV23 in PSD mice,27 identifying a potential therapeutic target for the treatment of PSD. Our recent study revealed the function of the NTS in the treatment of EA in PSD model mice and its indirect role in the motor efferent neural circuit dominated by M1 25.…”
mentioning
confidence: 96%
“…Previous studies indicate that acupuncture points for treating swallowing disorders after stroke include Lianquan (CV23), Tiantu (CV22), Chengjing (BL56), Chejia (ST6), Yifeng (TE17), Taixi (KI3), Fengchi (GB20), Neiguan (PC6), Sanyinjiao (SP6), Yintang (EX-HN3), Taiyang (EX-HN5), Jinjin (EX-HN12), Yuye (EX-HN13), Zusanli (ST36), Fenglong (ST40), Taichong (LR3), Xiaguan (ST7) ( 26 ). Among these, the most commonly used acupuncture points are Lianquan (CV23), Fengchi (GB20), Yifeng (TE17), Jinjin (EX-HN12), and Yuye (EX-HN13) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Lianquan (CV23) acupoint as a peripheral stimulation strategy, could improve the swallowing function in PSD model mice through the activation of motor cortex inputs to the NTS through the PBN. the application of EA-CV23 for the treatment of PSD by addressing how motor cortex activation benefits recovery of swallowing function via a subcortical pathway, suggesting that acupuncture treatment could be used as an effective therapeutic intervention to improve swallowing function ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of meridians and acupoints, acupuncture achieves therapeutic effects by inserting acupuncture needles into the corresponding acupoints. 113,114 Utilizing nano-delivery systems to incorporate biologically active ingredients onto the surface of stainless steel needles allows for the simultaneous release of these ingredients during the mechanical stimulation of acupuncture, thereby enhancing therapeutic efficacy. Xu and colleagues have made significant strides in the traditional acupuncture field by introducing a nanoenabled drug delivery acupuncture technology (nd-Acu) platform.…”
Section: Acupuncture and Nanodrug Delivery Systemsmentioning
confidence: 99%